Jeritan dari Lubang –Lubang Penyiksaan: Tambang Batu Bara Ombilin dalam Perspektif Humanis - Zubir, Zaiyardam (Universitas Andalas, 2024)
The Ombilin coal mine serves as an example of how natural resources can become a focal point of power struggles. This paper illustrates the dynamic movements among coal mine workers in Sawahlunto. Initially, the workers sought livelihood opportunities in the coal mines, while others were prisoners forced into labor by the colonial government. Over time, however, these mine workers transformed the site into a locus of nationalist movements, contributing to the broader history of Indonesia's journey toward independence. Thus, this paper provides a brief overview of how various locations and sites are interconnected through the broader discourses that developed during a particular period.